Use and Misuse of Nitrogen in Agriculture: The German Story - Rienk R. van der Ploeg; Rienk P. Schweigert; Rienk J. Bachmann (The Scientific World Journal, 2001)
Nitrogen (N) fertilization in agriculture has been discussed controversially in Germany for almost two centuries. The agronomist Carl Sprengel, who published his theory on the mineral nutrition of plants in 1828, advocated the use of mineral N fertilizers. Chemist Justus von Liebig, on the other hand, vehemently denied around 1850 the need for N fertilization. Although it soon became evident that Sprengel was right and Liebig was wrong, not much synthetic N fertilizer was used in German agriculture until around 1915, when the Haber-Bosch technique enabled the commercial production of NH3. The use of N fertilizers since then has grown, especially since 1950. To increase agricultural productivity, German governments have promoted, directly and indirectly, the use of N in crop and in animal production. Unfortunately, it was overlooked that N surpluses in agriculture increased rapidly; around 1980 they amounted yearly to more than 100 kg ha-1. The extensive use of N in agriculture is causing environmental damage and is contributing substantially to the external costs of present agriculture. The main N compounds that affect the environment are N2O, NH3, and NO3. These compounds are considered to contribute one third to the external costs of agriculture. Additionally, the high rate of human intake of animal proteins and lipids has adversely affected the health of the country’s population. Fundamental corrections in German farm policy appear inevitable.